Botswana - Accrual Accounting Policy Note and Guide - World Bank (Washington, DC, 2013)
This paper comprises two volumes: volume one, this concise policy and guidance note that deals with the request as outlined, and a volume two which provides more detailed technical guidance on the implementation of International Public Sector accounting Standards (IPSAS) accrual based standards. Recommended reforms directly relevant to this paper include: 1) fiscal reforms on both the revenue and expenditure sides to limit fiscal deficits and ensure a return to a sustainable medium term fiscal path; and 2) transforming the current planning and budget system which falls short in meeting the usual measures of budget effectiveness by, for example, moving towards government-wide medium term fiscal and expenditure frameworks and a program budget in the medium term, in tandem with public sector reform and the necessary changes to the Public Financial Management (PFM) legal framework and the government accounting system. Accrual accounting is a methodology under which transactions and other events are accounted for when they occur, and not only when the associated cash is received or paid. Following this methodology, revenues are accounted for when income is earned (and not just when the cash is received), and expenses are accounted when liabilities are incurred or resources consumed (and not just when cash is paid). As a consequence financial statements prepared on an accrual basis of accounting will not just report on cash balances, payments and receipts, but fully on all assets, liabilities, net assets/equity, revenue and expenses. This contrasts with the cash accounting methodology which recognizes transactions and other events only when cash is received or paid.